Assessing the Performance of Vessel Safety Inspectors of Maritime Safety Services Units in the Coast Guard Districts of Southern and Southeastern Mindanao - Aceron, Jamaal S. (Future Science / FSH-PH Publications, 2025)
Introduction: This study assessed the performance, motivation, and challenges of vessel safety inspectors in the Maritime Safety Services Units of the Coast Guard Districts of Southern and Southeastern Mindanao. It examined how operational conditions in maritime safety enforcement and qualifications of the inspectors affect their effectiveness. Method: The study determined the vessel safety inspectors’ age, sex, educational background, length of service, and inspection-related training, and correlate these factors with the six dimensions of performance: knowledge, skills, identity, context of performance, personal factors, and fixed factors. Their motivation was also assessed in terms of intrinsic and extrinsic influences. Results: Most inspectors are young, male, and degree holders in Criminology and Marine Transportation. Overall performance was “rated as Good” (89%) with strength in personal factors (93%) including professionalism and communication, and identity (90%) such as adherence to protocols and awareness. Areas for improvement includes critical thinking and fixed factors (86%) such as geographic constraints, policy limitations, and resources availability. Motivation was moderate (intrinsic mean = 3.45; extrinsic mean = 3.28). Experienced inspectors have higher motivation, particularly on external rewards. Operational conditions such as limited logistical support, inadequate training opportunities, and mobility constraints were the identified challenges in inspections. Conclusions: Vessel safety inspectors demonstrate competence despite operational challenges. Strengthening recruitment, targeted trainings, logistical support, motivation programs, and modern technology – anchored on a clear action plan will enhance efficiency, effectiveness, and aligning inspection practices with maritime safety policies and procedures.